Lampyris pseudozenkeri (Coleoptera, Lampyridae) new species to Greece and Europe - Fanti, Fabrizio; Vitali, Francesco (ENTOMOLOGIA HELLENICA, 2019)
Lampyris (s. str.) pseudozenkeri Geisthardt, 1999, a species closely related to Lampyris (s. str.) zenkeri Germar, 1817 and previously known from the south-western Turkey (Kuşadası, Aydın Province), is newly recorded from Kos Island (Dodecanese, Greece). This is the first record for Greece and Europe.